2016
DOI: 10.1080/19443994.2015.1031188
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization and mineralization of azo dye Acid Blue 113 by the UV/Oxone process and optimization of operating parameters

Abstract: A B S T R A C TA UV/Oxone advanced oxidation process was proposed to degrade and mineralize a synthesized Acid Blue 113 (AB113) dyeing wastewater. Various operating parameters which affected the removal efficiencies of AB113 and total organic carbon (TOC) such as reaction time, Oxone dosage, initial AB113 concentration, initial pH, and UV intensity were studied. Results presented effective removal of AB113 azo dye by UV/Oxone process based on both AB113 and TOC indicators. The reaction kinetics was shown to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The techniques, methods and procedures reported in literature for the remediation of AB113 dye can be broadly classified into biological-cum-chemical [13,20,21,28,51] electrocoagulation [39], physical methods using UV radiations [36,44,[46][47][48], photocatalytic degradation [66,74], low frequency ultrasound assisted degradation [40], nanomaterials [49] and use of inorganic materials including activated carbons [16,34,42,43,45,63]. Nevertheless, huge initial cost in installing operational plant, high-operational cost, regeneration problem, secondary pollutants, sensitivity to variations in wastewater input, interference by some wastewater constituents, and residual sludge generation are some associated problems in these methods [11,61].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques, methods and procedures reported in literature for the remediation of AB113 dye can be broadly classified into biological-cum-chemical [13,20,21,28,51] electrocoagulation [39], physical methods using UV radiations [36,44,[46][47][48], photocatalytic degradation [66,74], low frequency ultrasound assisted degradation [40], nanomaterials [49] and use of inorganic materials including activated carbons [16,34,42,43,45,63]. Nevertheless, huge initial cost in installing operational plant, high-operational cost, regeneration problem, secondary pollutants, sensitivity to variations in wastewater input, interference by some wastewater constituents, and residual sludge generation are some associated problems in these methods [11,61].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques, methods, and procedures have been reported in the literature, which are listed as electrocoagulation 1 , photocatalytic degradation 2 , 3 , biological–chemical procedures 4 – 13 , ultrasound methods with low frequency 14 , sono catalytic procedures 15 , 16 , and nanomaterials 17 , 18 . Various inorganic and nanomaterials are reported, of which activated carbon is widely used in textile industries 5 , 19 , 20 . These methods suffer from serious drawbacks such as the undesirable increase in operating expenses and overhead costs in the installation of plant and/or equipment, formation of degradation of the dye resulting in possible more toxic and hazardous secondary and tertiary pollutants, regeneration of the adsorbent resulting in high environmental and economic impact, inconsistency and large variation of the composition of the effluent, unwanted generation of the sludge are the few problems associated with the existing methods 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the adsorption behavior could be related to the valency forces through sharing of electrons between patulin and TETA‐WICF/MCR, via which the patulin may form a complex with active groups of TETA‐WICF/MCR (Peng et al., 2016). Also, k 2 value obtained from the pseudo‐second‐order model decreased with the increase of the initial patulin concentration, which suggested that the adsorption process could be independent of initial patulin concentration (Shu, Chang, & Huang, 2016).…”
Section: Resultsmentioning
confidence: 99%